2021
DOI: 10.1093/ndt/gfab238
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mild cognitive impairment in automated peritoneal dialysis patients

Abstract: Background Cognitive deterioration decreases quality of life, self-care and adherence to treatment, increasing mortality risk. There is scarce information of cognitive impairment in peritoneal dialysis, and data are controversial. Objective To determine the frequency and associated factors of cognitive impairment in patients on automated peritoneal dialysis (APD). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…CAS is not an independent risk factor for CI in patients undergoing PD. The prevalence of CI based on MoCA scores in this PD population was 56%, which is similar to the percentages reported by Salazar-Felix [51] and Yi et al [52] (65% and 49.9%, respectively). In addition, a systematic review and meta-analysis showed that the prevalence of CI in patients undergoing PD ranged from 3.3% to 74.5% [53], which could be attributed to the different neuropsychological tests used.…”
Section: Discussionsupporting
confidence: 89%
“…CAS is not an independent risk factor for CI in patients undergoing PD. The prevalence of CI based on MoCA scores in this PD population was 56%, which is similar to the percentages reported by Salazar-Felix [51] and Yi et al [52] (65% and 49.9%, respectively). In addition, a systematic review and meta-analysis showed that the prevalence of CI in patients undergoing PD ranged from 3.3% to 74.5% [53], which could be attributed to the different neuropsychological tests used.…”
Section: Discussionsupporting
confidence: 89%
“…It seems that the CI of patients on RRT may be underdiagnosed. Moreover, little is known about the prevalence of CI in patients undergoing PD [12] . Patients on PD with cognitive problems might not be able to continue this form of dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Dialysis patients have a high burden of vascular disease, and cognitive impairment from cerebrovascular disease is common in patients undergoing either hemodialysis )HD( or peritoneal dialysis )PD(. 12 The pathophysiology may be attributed to microinflammation, malnutrition, and uremic metabolites. [12][13][14] Detecting cognitive impairments in dialysis patients is imperative.…”
mentioning
confidence: 99%
“…12 The pathophysiology may be attributed to microinflammation, malnutrition, and uremic metabolites. [12][13][14] Detecting cognitive impairments in dialysis patients is imperative. Lee et al 9 found that patients with varying degrees of severity of cognitive impairment are likely to go unnoticed and probably don't voice any concerns.…”
mentioning
confidence: 99%
See 1 more Smart Citation